PREVENTIVE STRATEGIES IN THE STAGES OF FORMATION AND COURSE OF BRONCHOPULMONARY DYSPLASIA - I. V. Davydova; L. S. Namazova-Baranova; G. V. Yatsyk; N. A. Mayanskiy; E. P. Zimina; A. S. Ostrovskaya (Педиатрическая фармакология)
Prevention of development of bronchopulmonary dysplasia (BPD) and possibility of preventing severe course of the disease are the first-priority areas of neonatal pulmonology. Use of modern medical technologies allows protecting a premature infant’s respiratory system from as early as antenatal period of development. Use of the newest neonatal resuscitation protocols may prevent development of BPD. International experience and clinical data gathered by the authors demonstrate that seasonal palivizumab immune prevention of severe course of a respiratory syncytial viral infection in children with BPD results in rarer cases of hospitalization, resuscitation measures and fatal outcomes. The article presents modern preventive strategies used in this category of patients.